2022
DOI: 10.1021/acschembio.1c00839
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the Sphingolipid Inhibitors Sphingofungins in Filamentous Fungi Requires Aminomalonate as a Metabolic Precursor

Abstract: Sphingofungins belong to a group of structurally related sphingolipid inhibitors produced by fungi, which specifically inhibit serine palmitoyl transferases, enzymes catalyzing the initial step during sphingolipid biosynthesis. Sphingolipids are integral parts of the eukaryotic cell membrane, and disturbances in their homeostasis have been linked to various human diseases. It has been suggested that external interventions, via sphingolipid inhibitors, may represent a promising approach for alternative therapie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…We then proceeded to compare the inhibitory activity of sphingofungin B (1) with sphingofungin C (2) and the novel sphingofungin derivatives B 2 (3) and C 2 (4) ( 17 ) ( Fig. 3A ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We then proceeded to compare the inhibitory activity of sphingofungin B (1) with sphingofungin C (2) and the novel sphingofungin derivatives B 2 (3) and C 2 (4) ( 17 ) ( Fig. 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…Sphingofungins C 3 (5) and C 4 (6) were detected in extracts obtained from the previously created strain A. fumigatus xyl-G sphAPv ( 17 ) via HPLC-HRMS and tandem high-resolution mass spectrometry (HRMS 2 ) analyses (Fig. S5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The biosynthetic gene cluster for the production of sphingofungins, such as sphingofungin B 29 , have been elucidated in Aspergillus fumigatus . 22 In vitro analysis showed that the first key step involves the condensation of a C18 polyketide with an aminomalonate substrate, using the aminotransferase SphA.…”
mentioning
confidence: 99%